2019
DOI: 10.14569/ijacsa.2019.0100535
|View full text |Cite
|
Sign up to set email alerts
|

LBPH-based Enhanced Real-Time Face Recognition

Abstract: Facial recognition has always gone through a consistent research area due to its non-modelling nature and its diverse applications. As a result, day-to-day activities are increasingly being carried out electronically rather than in pencil and paper. Today, computer vision is a comprehensive field that deals with a high level of programming by feeding the input images/videos to automatically perform tasks such as detection, recognition and classification. Even with deep learning techniques, they are better than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 17 publications
0
22
0
2
Order By: Relevance
“…Concerning face recognition, LBPH outperformed eigenfaces using the proposed framework with the hardware and the control environment setting. The results show that LBPH is robust in greyscale and illumination in real time [15,18,22]. It is also observed that the eigenfaces have difficulties in recognizing faces in a situation where the position of the face is similar across images of different subjects.…”
Section: Figure 2 Mask Detection and Face Detectionmentioning
confidence: 84%
“…Concerning face recognition, LBPH outperformed eigenfaces using the proposed framework with the hardware and the control environment setting. The results show that LBPH is robust in greyscale and illumination in real time [15,18,22]. It is also observed that the eigenfaces have difficulties in recognizing faces in a situation where the position of the face is similar across images of different subjects.…”
Section: Figure 2 Mask Detection and Face Detectionmentioning
confidence: 84%
“…Local Binary Pattern Histogtram (LBPH) adalah sebuah kombinasi algoritma antara LBP dengan Histogram of Oriented Gradients(HOG) [14]. LBPH merupakan penyempurnaan performa dari LBP dalam proses face recognition.…”
Section: Selain Itu Terdapat Beberapa Metode Lain Yang Saat Ini Sedang Berkembang Seperti Speeded Up Robust Feature (Surf) Histogram Of Ounclassified
“…Many methods can be used to recognize the face from a digital image. Local Binary Patterns Histogram (LBPH) method is one of the most useful techniques in face recognition procedures [19]. It divides a picture into a number of small regions and extracts the features from each one.…”
Section: -3-human Face Detection and Recognition Techniquementioning
confidence: 99%